Wild emmer wheat, the progenitor of modern bread wheat, exhibits great diversity in the VERNALIZATION1 gene - Strejčková, Beáta; Mazzucotelli, Elisabetta; Čegan, Radim; Milec, Zbyněk; Brus, Jan; Çakır, Esra; Mastrangelo, Anna Maria; Özkan, Hakan; Šafář, Jan (Frontiers in Plant Science, 2023)
Wild emmer wheat is an excellent reservoir of genetic variability that can be utilized to improve cultivated wheat to address the challenges of the expanding world population and climate change. Bearing this in mind, we have collected a panel of 263 wild emmer wheat (WEW) genotypes across the Fertile Crescent. The genotypes were grown in different locations and phenotyped for heading date. Genome-wide association mapping (GWAS) was carried out, and 16 SNPs were associated with the heading date. As the flowering time is controlled by photoperiod and vernalization, we sequenced the VRN1 gene, the most important of the vernalization response genes, to discover new alleles. Unlike most earlier attempts, which characterized known VRN1 alleles according to a partial promoter or intron sequences, we obtained full-length sequences of VRN-A1 and VRN-B1 genes in a panel of 95 wild emmer wheat from the Fertile Crescent and uncovered a significant sequence variation. Phylogenetic analysis of VRN-A1 and VRN-B1 haplotypes revealed their evolutionary relationships and geographic distribution in the Fertile Crescent region. The newly described alleles represent an attractive resource for durum and bread wheat improvement programs.